PENGARUH PEMODERASI GENDER DAN JENIS PEKERJAAN PADA HUBUNGAN ANTARA ORGANIZATIONAL TENURE DAN KOMITMEN ORGANISASIONAL - Mellisa Claudia; Hidajat Hendarsjah (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2021)
This research aims to find out the effect of organizational tenure on the organizational commitment of employees in the textile and garment industries. The implication of the article was useful to inspire managers in preparing strategies to increase organizational commitment and to develop the employees. This research used 129 samples from textile and garment’s employee. Research methods that had been used are the regression test and the subgroup analysis. The result of the research was the affective, normative and continuance organizational commitment was not influenced by organizational tenure. White-collar occupational group, blue-collar occupational group, female gender, and male gender was not the moderation variable. The finding that we had is the organizational commitment was not influenced by organizational tenure, but the affective, normative and continuance organizational commitment was influenced by occupational group and gender. Keywords: organizational tenure, affective commitment, normative commitment, continuance commitment, gender